Avaliação nutricional da casquinha de milho em dietas para coelhos em crescimento - Ribeiro, Bruna Pontara Vilas Boas; Machado, Luiz Carlos; Geraldo, Adriano; De Medeiros, Alex Thaironi; Martins, Marcelo Gaspary; Dos Santos, Tiago Antônio [UNESP] (My University, 2013)
For efficient balance of complete feeds for rabbits is essential to research the nutritional value of alternative ingredients as well as the substitution capacity of the traditional ingredients. This study aimed to evaluate the effect of replacing alfalfa hay by corn hulls (pericarp) and to determine the nutritional value of this ingredient for growing rabbits. For the performance evaluation, we used 30 new zealand white animals. The considered period was of 35 to 72 days of age. The treatments consisted of five diets, being one reference and four with increasing levels of substitution of alfalfa hay bay the corn hulls (25, 50, 75 and 100%). To determine the nutritional value a digestibility assay was carried using 18 new zealand white rabbits distributed in a reference diet and other test diet, where the corn hulls replaced 20% of the reference diet being determined the values of digestible energy (DE) and digestible protein (DP). No significant differences were observed for final weight, average daily gain and feed intake. Feed conversion was improved by the inclusion of the corn hulls, with a decreasing linear effect (P <0.01). The best value for feed conversion was observed at 100% inclusion of corn hulls. It was found that this alternative ingredient presents 1832.9 kcal DE/kg and 2.32% of PD, being these values were expressed on a dry basis. The cone hulls can replace alfalfa hay in diets for growing rabbits.
Use of the cone corn for growing rabbits
Keywords: Alfalfa hay; Alternative feed; Nutritional value and corn hulls; Rabbit nutrition